A STUDY ON THE ABILITY OF THE FIRST GRADE STUDENTS OF SMK LABOR PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXTS, REPORT TEXTS AND RECOUNT TEXTS - Nathaya Rakha Anisah; Fakhri Ras; Erni Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aimed to find out the ability of the students in comprehending descriptive text, report text, and recount text in reading comprehension. It has been conducted at SMK Labor Pekanbaru. The total number of population was 8 classes, with the total number of students was 247. The try-out class was X Accounting 3 with the total number of 20 students. The sample class was X Accounting 2 with the number of total 35 students. The try-out class and the sample class chosen by cluster random sampling. The researcher constructed the instrument in multiple choices. The result showed that the ability of the first grade students of SMK Labor Pekanbarun in comprehending Descriptive text, Report text, and Recount text can be categorized into good level with the mean score 62. The students’ highest score was in finding factual information with the mean score 64.8. On the other hand the lowest score that students got was finding meaning of vocabulary with the mean score of 55.7. Meanwhile, the other aspects were such as finding main idea with the mean score of 64.3, finding the reference and inference were at the same mean score 62.4, finding social function with the mean score 64.3, and finding language features with the mean score 59.5. The suggestions are the reading instruction should focus on reading comprehension abilit y for the sake of providing suitable strategies, positive contributions and increase of reading archievement. In other words, the Reading Comprehension of the first grade students of SMK Labor Pekanbaru was in good level.Key Words: Student’s Ability, Descriptive Text, Report Text, Recount Text